Microfossils in surface sediments of brackish waters from the South African west coast - Sascha Fürstenberg; Nadine Gründler; Stephanie Meschner; Peter Frenzel (PANGAEA, 2017)
A faunistic survey covering 25 sites in estuaries, coastal lakes and ponds along the west coast of South Africa between the Cape of Good Hope in the south and the Olifants River in the north was carried out in May 2014. The study aimed to establish a dataset with ecological and distribution data of ostracods and foraminifers for later palaeoenvironmental reconstructions. Canonical correspondence analysis showed that the distribution of the 19 foraminifer and 32 ostracod taxa was controlled mainly by habitat structure, but that specific conductivity (salinity) was best and solely described by the second axis, highlighting the usefulness of the two microfossil groups for salinity reconstructions. Habitat structure was demonstrated by the foraminifer species Trochamminita irregularis extquotesingle preference for stillwater areas of lakes. Sarscypridopsis aculeata and Sarscypridopsis glabrata were the dominant ostracod species in coastal ponds and lakes. However, their living distributions excluded each other, with S. aculeata preferring areas of lower salinity and S. glabrata dominating areas of higher salinity up to hyperhaline conditions in small, closed water bodies.
Supplement to: Fürstenberg, S et al. (2017): Microfossils in surface sediments of brackish waters on the west coast of South Africa and their palaeoecological implications. African Journal of Aquatic Science, 42(4), 329-339, https://doi.org/10.2989/16085914.2017.1406326